A formação dos bons professores universitários para licenciatura de Ciências Biológicas : caminhos que possibilitam essa construção - Dutra, Leandro Barreto (2020)
The research had as general objective to understand the formative paths that led the good teachers of a Degree course in Biological Sciences to be who they are and, through this understanding, to highlight practical principles that could guide the experimentation of teaching to other teachers. It can be characterized as a mixed research of concomitant nested model, of a nature applied with field procedures performed in a public university in the city of Manaus. After the literature review on research involving the theme of the good teacher, it was possible to consider this thesis unprecedented by the characterization of the research added to the perception of students on the theme and also considering the life trajectory of the good teachers pointed out by these students. The central support of the thesis is in Jerome Bruner and in his concepts of narrative, meaning construction and popular pedagogy. The doctoral work can be divided into three stages: the first involves the perception of students about the concept of good teacher; the second involves the autobiographical narrative of the good teachers of the course appointed by the students and the third the focus group conversation with the same teachers The results of the students point in general to a complex of characteristics that good teachers must possess, evidencing five: mastering the content, mastering didactics, understanding students, having a good relationship with students and being motivating. The autobiographical narratives reconstructed by the researcher point to a professional development of teachers in the sense of approximation of the cultural model of a good teacher. It was possible to identify three phases in this development: denial; transformation and affirmation. Still analyzing the trajectory of life, four formative marks were identified: the development of responsibility and commitment to oneself and to the other; differentiated activities in the disciplines of compulsory supervised internship; the affective relationship with the content taught and; the porosity and sensitivity in the encounter with the other. These marks enabled the three teachers to become the teachers they are today and who in practice demonstrate some care in their professional practice in three moments: in the preparation of classes they strive to master the content, to find differentiated activities and listen to the students; in the classes they seek the contextualization of the subjects with the daily lives of the students, seek different resources to complement their action and propose the formation of communities of apprentices and; in the after-class, teachers reflect on what happened in order to replan the next actions seeking learning. The intention to reflect on good teachers is not in the sense of creating universal models to be copied, but of pointing out possible and close models of the cultural canon of the good teacher so that other teachers feel driven to experience themselves in this process of being and becoming teachers.